2019
DOI: 10.1021/acsomega.9b02642
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Multifunctional Surface Chemistry of Reduced Graphene Oxide via Combined Elemental Doping and Chemical Modifications

Abstract: The synthesis of graphene materials with multiple surface chemistries and functionalities is critical for further improving their properties and broadening their emerging applications. We present a simple chemical approach to obtain bulk quantities of multifunctionalized reduced graphene oxide (rGO) that combines chemical doping and functionalization using the thiol-ene click reaction. Controllable modulation of chemical multifunctionality was achieved by simultaneous nitrogen doping and gradual chemical reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 61 publications
(148 reference statements)
2
25
0
Order By: Relevance
“…In the clinical trial, trastuzumab in combination with adriamycin demonstrated significant efficacy, while highly dose-dependent cardiotoxicity was a problem that has to be solved [ 8 ]. Sustained release of chemotherapy agents at the tissue of cancer target is recognized as a good solution to lower doses required for therapeutic efficacy and improve the safety profiles [ 9 ]. To achieve better antitumour efficacy but fewer side effects, there is an urgent need to improve anticancer drug delivery efficiency in targeting cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical trial, trastuzumab in combination with adriamycin demonstrated significant efficacy, while highly dose-dependent cardiotoxicity was a problem that has to be solved [ 8 ]. Sustained release of chemotherapy agents at the tissue of cancer target is recognized as a good solution to lower doses required for therapeutic efficacy and improve the safety profiles [ 9 ]. To achieve better antitumour efficacy but fewer side effects, there is an urgent need to improve anticancer drug delivery efficiency in targeting cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…A notably increased atomic concentration of nitrogen (6.26 at %) and sulfur (4.79 at %) on FG-CYS, relative to pristine graphene, implied successful grafting of thiol precursor on the surface of graphene. As depicted in Figure 3 b, the doublet peaks of S2p 3/2 and S2p 1/2 at around 164.1 eV and 165.2 eV, respectively, can be assigned to thioether sulfur bonded to carbon (C–S–C) species on the narrow XPS spectra of S2p of FG-CYS, and confirmed the successful attachment of the thiol groups from the thiol precursor via thiol-ene click reaction on the surface of the graphene [ 18 , 19 ]. Meanwhile, S2p 3/2 and S2p 1/2 peaks with lower intensities deconvoluted at 164.8 eV and 166.1 eV, respectively, could be ascribed to C–S or S–S species on the surface of graphene [ 20 ].…”
Section: Resultsmentioning
confidence: 72%
“…Losic et al. tailored the surface properties of rGO through elemental doping and post‐synthetic thiol‐ene modification . The doping process occurred during reduction with ammonia and hydrazine, which resulted in N‐doped GO sheets.…”
Section: Exfoliation Approachesmentioning
confidence: 99%